2016
DOI: 10.1111/mmi.13556
|View full text |Cite
|
Sign up to set email alerts
|

The Group A Streptococcus serotype M2 pilus plays a role in host cell adhesion and immune evasion

Abstract: Group A Streptococcus (GAS), or Streptococcus pyogenes, is a human pathogen that causes diseases ranging from skin and soft tissue infections to severe invasive diseases, such as toxic shock syndrome. Each GAS strain carries a particular pilus type encoded in the variable fibronectin-binding, collagen-binding, T antigen (FCT) genomic region. Here, we describe the functional analysis of the serotype M2 pilus encoded in the FCT-6 region. We found that, in contrast to other investigated GAS pili, the ancillary pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 69 publications
(98 reference statements)
1
37
0
Order By: Relevance
“…This possibility is further suggested by the existence of a close R28 homolog in group B streptococci that commonly colonize the vaginal epithelium (30). The acquisition of the tee89 gene in emergent clade 3 emm89 may have conferred new functional adherence or immune evasion properties (3,36,41). The recent increased superantigen complement in emm1 subclones described in China is reason for increased awareness of the enhanced virulence potential imposed by already impactful iGAS strains, wherein emm12 strains facilitated the horizontal transfer of scarlet fever-associated mobile elements carrying speC and ssa to the emm1/ST28 lineage (33).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is further suggested by the existence of a close R28 homolog in group B streptococci that commonly colonize the vaginal epithelium (30). The acquisition of the tee89 gene in emergent clade 3 emm89 may have conferred new functional adherence or immune evasion properties (3,36,41). The recent increased superantigen complement in emm1 subclones described in China is reason for increased awareness of the enhanced virulence potential imposed by already impactful iGAS strains, wherein emm12 strains facilitated the horizontal transfer of scarlet fever-associated mobile elements carrying speC and ssa to the emm1/ST28 lineage (33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a disruptive inversion of the FimIV locus, which encodes a putative pilus in many strains of S. zooepidemicus [5], was shown to be mediated by PinR [32]. Hair-like pilus structures on the surface of streptococci can play important roles in the adhesion and survival of streptococci [36,37], but can also be targeted as components of subunit vaccines [29]. Therefore, the reversible regulation of FimIV could assist S. zooepidemicus to successfully fulfil its opportunistic lifestyle.…”
Section: The Price Of Persistencementioning
confidence: 99%
“…Other studies have reported that the GAS pilus alters the susceptibility of GAS to phagocytosis in whole human blood by either increased bacterial killing (M1T1 strain; FCT-2, emm pattern A-C) or decreased bacterial killing (M2T2 strain; FCT-6, emm pattern E) (33,34). The emm pattern D strain Alab49 expresses the FCT-3 form of pili (T serotype T3/13/B) (7).…”
Section: Surface Proteins Of Group a Streptococcimentioning
confidence: 99%